Dose–response correlation for CAR-T cells: a systematic review of clinical studies - Christopher Heery; Matthew J Frigault; Bijal Shah; Anand Rotte; Ayub Ansari; Brad Gliner (Journal for ImmunoTherapy of Cancer, 2022)
The potential of chimeric antigen receptor (CAR) T cells to successfully treat hematological cancers is widely recognized. Multiple CAR-T cell therapies are currently under clinical development, with most in early stage, during which dose selection is a key goal. The objective of this review is to address the question of dose-dependent effects on response and/or toxicity from available CAR-T cell clinical trial data. For that purpose, systematic literature review of studies published between January 2010 and May 2022 was performed on PubMed and Embase to search clinical studies that evaluated CAR-T cells for hematological cancers. Studies published in English were considered. Studies in children (age <18 years), solid tumors, bispecific CAR-T cells and CAR-T cell cocktails were excluded. As a result, a total of 74 studies met the inclusion criteria. Thirty-nine studies tested multiple dose levels of CAR-T cells with at least >1 patient at each dose level. Thirteen studies observed dose-related increase in disease response and 23 studies observed dose-related increase in toxicity across a median of three dose levels. Optimal clinical efficacy was seen at doses 50–100 million cells for anti-CD19 CAR-T cells and >100 million cells for anti-BCMA CAR-T cells in majority of studies. The findings suggest, for a given construct, there exists a dose at which a threshold of optimal efficacy occurs. Dose escalation may reveal increasing objective response rates (ORRs) until that threshold is reached. However, when ORR starts to plateau despite increasing dose, further dose escalation is unlikely to result in improved ORR but is likely to result in higher incidence and/or severity of mechanistically related adverse events.